Apoptosis induced in Jurkat cells by several agents is preceded by intracellular acidification. - Gottlieb, R A (1996)
We have previously shown that in neutrophils deprived of granulocyte colony-stimulating factor, apoptosis is preceded by acidification and that the protection against apoptosis conferred on neutrophils by granulocyte colony-stimulating factor is dependent upon delay of this acidification. To test the hypothesis that acidification could be a general feature of apoptosis, we examined intracellular pH changes in another cell line. Jurkat cells, a T-lymphoblastoid line, were induced to undergo apoptosis with anti-Fas IgM, cycloheximide, or exposure to short-wavelength UV light. We found that acidification occurred in response to treatment with these agents and that acidification preceded DNA fragmentation. Jurkat cells were also found to possess an acid endonuclease that is active below pH 6.8, compatible with a possible role for this enzyme in chromatin digestion during apoptosis. Incubation of the cells with the bases imidazole or chloroquine during treatment with anti-Fas antibody or cycloheximide or after UV exposure decreased apoptosis as assessed by nuclear morphology and DNA content. The alkalinizing effect of imidazole and chloroquine was shown by the demonstration that the percentage of cells with an intracellular pH below 6.8 after treatment with anti-Fas antibody, cycloheximide, or UV was diminished in the presence of base as compared with similarly treated cells incubated in the absence of base. We conclude that acidification is an early event in programmed cell death and may be essential for genome destruction.